Typhoid fever with severe abdominal pain: diagnosis and clinical findings using abdomen ultrasonogram, hematology-cell analysis and the Widal test - Arjunan, Maripandi; Al-Salamah, Ali A. (The Journal of Infection in Developing Countries, 2010)
A six-year-old boy with high-grade fever and abdominal pain in the epigastric region was examined with ultrasonogram of the abdomen. Hematology-cell analysis, serology (Widal test), urine analysis, and blood cultures were also performed. The ultrasonogram was helpful for the identification of multiple organ involvement with Salmonella typhi. The results revealed mild hepatosplenomegaly, minimal ascitis, and mesenteric lympoadenopathy. Hematological analysis showed a white blood count of 6,300 cells mL-1; a red blood cell count of 4.54 million/cu mm. The erythrocyte sedimentation rate (ESR) was 24 mm/1 hr; hemoglobin level of 11.5 g/dl; and a platelet count of 206,000 cells/mL. The patient's serum was agglutinated with lipopolysaccharide (TO), the titre value was 1:320 dilution, and flagellar antigen (TH) titre was 1:640. The patient was diagnosed with typhoid fever. Ceftriaxone was given intravenously for five days and the patient fully recovered.